Potensi Invasif Ikan Louhan (Flowerhorn) di Waduk Lahor Malang - Sri Andayani; Liga Insani; Rima Oktavia Kusuma; Muh. Sulaiman Dadiono (Indo Journal of Multidisciplinary Science, 2025)
Flowerhorn fish is a predatory fish that is a cross between Cichlasoma, Paraneetroplus and Amphilophus. In Indonesian waters, flowerhorn fish is very dangerous to the local ecosystem because it can be the main predator. This study reports the catch of flowerhorn fish in large numbers in Lahor Reservoir, Malang, East Java, so it has the potential to become an invasive fish. The research method uses a desk study method with secondary data and field observations by sources. The catch of flowerhorn fish in Lahor Reservoir is an important note to maintain the natural ecosystem of the reservoir from the invasiveness of this fish. Flowerhorn fish species in Lahor Reservoir must be mapped, monitored and regulated with strict rules so that the balance of the reservoir ecosystem is maintained. A description of the morphology of the flowerhorn fish species caught is included in the discussion.